Autoimmune encephalitis positive for both anti-γ-aminobutyric acid B receptor and anticollapsin response-mediator protein 5 antibodies: A case report. Issue 3 (January 2018) - Xia, Junyang; Yin, Xiaoming; Zhu, Mingqin; Cao, Jie; Song, Xiaonan
Abstract: Rationale: Autoimmune encephalitis (AE) is a heterogeneous group of recently identified disorders. Despite severe and even prolonged neurologic deficits, dramatic improvements may occur with proper immunotherapy in some patients with AE. Antineuronal antibodies have been discovered in patients' serum and cerebrospinal fluid (CSF). However, AE with multiple antineuronal antibodies is rare. To date, there are no published reports of AE with both anti-γ-aminobutyric acid B receptor (GABAB R) and anticollapsin response-mediator protein 5 (CV2) antibodies. Patient concerns: We describe a 46-year-old man who presented with seizures, working memory deficits, and visual hallucinations. We detected anti-CV2 and anti-GABAB R antibodies in his serum and CSF. Brain magnetic resonance imaging (MRI) revealed patchy abnormal signals in his left temporal lobe and hippocampus. The patient's symptoms improved after receiving intravenous immunoglobulin injections and glucocorticoids, but his condition relapsed within 4 months, and he was readmitted to our hospital. Repeated MRI scans revealed new lesions in his right temporal lobe and hippocampus. Diagnosis: The AE diagnosis was established from the results of the preliminary physical examination, the laboratory tests, and the imaging findings. Interventions: The patient received intravenous immunoglobulins and glucocorticoids. Outcomes: We followed the patient for 9 months from the date of the patient's second hospital discharge. He experienced no seizures during this period, but his short-term memory deficits and visual hallucinations were not completely alleviated. Lessons: Coexisting anti-CV2 and anti-GABAB R antibodies may have synergistic effects and worsen the clinical syndrome. AE with multiple antineuronal antibodies may be relapse-prone. Further studies investigating the relationship between anti-CV2 and anti-GABAB R antibodies are warranted.